PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN PERSEPSI HARGA TERHADAP NILAI PELANGGAN DALAM MENINGKATKAN MINAT BELI (Studi Pada Konsumen Produk Batu Potong Besi 4 Inch Merek Wd Di Jawa Tengah) - Kurniawan, Hendy; Soesanto, Harry; Yuniawan, Ahyar (Master of Management Diponegoro University, 2016)
Technological development in the world makes the competition tighter in the metal cutting industry. With the increasing number of brand choice of 4 inch Metal cutting disc product, it increases the number of choices for people to buy a metal cutting disc at a cheaper price and better quality. The 4 inch WD metal cutting disc product is able to lead the market in Indonesia with the right marketing strategy, so it can increase the customer purchase intention continuously. The purpose of this research is to analyze the influence of product quality, service quality and perceived price on customer value in increasing purchase intention of the 4 inch WD metal cutting disc product.The object of this research is a purchase decision maker of the 4 inch WD metal cutting disc product in Central Java, especially in the town of Magelang, Kudus and Purwodadi. The research uses a proportional random sampling technique with 155 respondents. A conceptual model is developed for this research with four hypotheses, which will be analyzed by using Structural Equation Modeling (SEM) by AMOS 23 Software.The result of SEM analysis for the full model meets the criteria of goodness of fit. So, it could be said that the model is properly used. The result of this research shows that perceived value will increase by increasing product quality, service quality, and perceived price. Furthermore, increased perceived value will increase purchase intention of the 4 inch WD metal cutting disc product.